Starbucks: Adapting in the Indian Market - Mahobia, Himanshu; Jain, Trilok Kumar (Indian Journal of Marketing, 2015)
Starbucks is a coffee retail chain based in the United States of America and is expanding its global footprint by increasing its presence in the Indian market. The Indian market is quite different as the coffee consumption in India is very low - with consumption of only 82 grams per capita as compared to 4 kilograms per capita in the USA. Research in India has indicated that most people go to a cafÃ© to socialize and form stronger personal and business relationships, and not merely for drinking coffee. Realizing this trend, Starbucks has customized its store ambience along with customization of its product offerings. To penetrate the price sensitive Indian market, the products are also priced lower as compared to the prices in the USA, but the prices have been kept relatively high as compared to major competitors like CafÃ© Coffee Day and Barista Lavazza. The case analyzed the evolution of Starbucks and its global vision and strategy, the challenges faced by it in India, and why and how Starbucks is adapting to the local tastes and preferences, is expanding its footprint aggressively to combat the competition and is also maintaining its premium imagery as the low price strategy may dilute its global brand appeal. The real challenge for the company in India is penetrating the coffee retail market and developing superior offerings through adaptation.